Orientation dependence of the ionization of CO and NO in an intense femtosecond two-color laser field - Li, H.; Ray, D.; De, S.; Znakovskaya, I.; Cao, W.; Laurent, G.; Wang, Z.; Kling, M. F.; Le, A. T.; Cocke, C. L. (My University, 2011)
Two-color (800- and 400-nm) short (45-fs) linearly polarized pulses are used to ionize and dissociate CO and NO. The emission of Cq+, Nq+, and O+ fragments indicates that the higher ionization rate occurs when the peak electric field points from C to O in CO and from N to O in NO. This preferred direction is in agreement with that predicted by Stark-corrected strong-field-approximation calculations.